Identification of Psychological Conditions and Feelings of Fatigue Among Employees at Makassar Air Traffic Service Center - Saleh, Lalu Muhammad; Russeng, Syamsiar S.; Tadjuddin, Istiana; Yanti, Iva Hardi; Syafitri, Nurul Mawaddah; Rahmadani, Yulianah; Yusbud, Mahfuddin (Media Kesehatan Masyarakat Indonesia, 2023)
Air Traffic Control (ATC) remains an active field of work during the pandemic due to the demand from domestic and international travelers. It is crucial for controllers to prioritize both their mental health while on duty and their body's immunity against conditions that make them vulnerable to Covid-19. Therefore, this study aims to review psychological conditions, feelings of fatigue, and quality of life among ATC during the pandemic. A cross-sectional descriptive design was used and the participants were 89 ATC in Makassar Air Traffic Service Center. The data collected included the general characteristics of ATC, DASS-21, KAUPK2, and (WHOQOL)-BREF. Data were collected from February to March 2022, then analysis was carried out using SPSS and Excel software. The results indicated the presence of negative emotional conditions among ATC even outside of their normal traffic control duties. Approximately 24% of ATC reported feelings of fatigue, while the quality of life exhibited a wide distribution of data, ranging from moderate to low. Therefore, it was concluded that the health status of ATC, even with regulations limiting the amount of traffic related to the pandemic period, still needs special attention to maintain performance.